Gradient‐induced voltages on 12‐lead ECGs during high duty‐cycle MRI sequences and a method for their removal considering linear and concomitant gradient terms. Issue 5 (23rd June 2015) - Zhang, Shelley HuaLei; Tse, Zion Tsz Ho; Dumoulin, Charles L.; Kwong, Raymond Y.; Stevenson, William G.; Watkins, Ronald; Ward, Jay; Wang, Wei; Schmidt, Ehud J.
Abstract : Purpose: To restore 12‐lead electrocardiographic (ECG) signal fidelity inside MRI by removing magnetic field gradient‐induced voltages during high gradient duty cycle sequences. Theory and Methods: A theoretical equation was derived to provide first‐ and second‐order electrical fields induced at individual ECG electrodes as a function of gradient fields. Experiments were performed at 3T on healthy volunteers using a customized acquisition system that captured the full amplitude and frequency response of ECGs, or a commercial recording system. The 19 equation coefficients were derived via linear regression of data from accelerated sequences and were used to compute induced voltages in real‐time during full resolution sequences to remove ECG artifacts. Restored traces were evaluated relative to ones acquired without imaging. Results: Measured induced voltages were 0.7 V peak‐to‐peak during balanced steady state free precession (bSSFP) with the heart at the isocenter. Applying the equation during gradient echo sequencing, three‐dimensional fast spin echo, and multislice bSSFP imaging restored nonsaturated traces and second‐order concomitant terms showed larger contributions in electrodes further from the magnet isocenter. Equation coefficients are evaluated with high repeatability (ρ = 0.996) and are dependent on subject, sequence, and slice orientation. Conclusion: Close agreement between theoretical and measured gradient‐induced voltages allowed for real‐time removal. Prospective estimation of sequence periods in which large induced voltages occur may allow hardware removal of these signals. Magn Reson Med 75:2204–2216, 2016. © 2015 Wiley Periodicals, Inc.